Letters of Robert Grosseteste, Bishop of Lincoln - Grosseteste, Robert, 1175?-1253 (Book collections on Project MUSE., 2010)
This volume contains the first complete translation of Grosseteste's collected Latin letters and shows that these were most likely chosen and arranged by Grosseteste himself. Shedding light on some of the period's crucial debates on issues of theology, law, pastoral care, and episcopal authority, Frank Mantello and Joseph Goering's richly annotated English translation makes his letters more accessible than ever for scholars and students, and for those interested in medieval history, religion, and culture"--Jacket.